Synthesis of Phenanthrenes by Cationic Chromium(III) Porphyrin-Catalyzed Dehydration Cycloaromatization - Wakabayashi, Ryota; Kurahashi, Takuya; Matsubara, Seijiro (Synlett, 2013)
Readily available biphenyl derivatives with ortho oxirane moiety react in the presence of cationic chromiun(III) porphyrin catalyst to afford phenanthrenes. The reaction is considered to be triggered by activation of the oxirane moiety through coordination to the Lewis acidic cationic chromium to give aldehyde via 1,2-hydride shift, which reacts with arene through intramolecular electrophilic aromatic substitution and subsequent dehydration. The reaction allows constructing a variety of polycyclic aromatic and heteroaromatic compounds.
Keywords: arene; chromium; cyclization; porphyrin; transition metals